Financial management of an environmental enterprise - E. A. Kirova; A. A. Kurchenko (Вестник университета)
The article examines financial management of environmental enterprises from the standpoint of evaluating the results of financial analysis and specifics of its implementation. Increasing the competitiveness of environmental organisations in the Russian Federation and ensuring their prospects in the face of sanctions and restrictions at this stage of development is becoming increasingly relevant. The authors propose a methodology for financial analysis of industrial and environmental activities of an enterprise based on the calculation of key financial and private environmental indicators of environmental enterprises. The novelty of this study lies in an integrated approach to financial management based on the results of the analysis of financial and private environmental indicators of environmental organisations, covering the financial and environmental aspects of their activities. The integrated approach to financial management is innovative because it is founded on the close relationship between financial and environmental activities of enterprises. The presented article develops analytical support and methodological tools of the analysis for use by environmental enterprises, with consideration to their specifics, in order to improve the efficiency of financial management. The practical significance of this article lies in the analytical provision of effective financial management for the sustainable development of environmental enterprises.